2023
DOI: 10.3390/electronics12132857
|View full text |Cite
|
Sign up to set email alerts
|

Word-of-Mouth Engagement in Online Social Networks: Influence of Network Centrality and Density

Abstract: This paper investigates the effect of network centrality and network density on the propensity to engage in positive and negative eWOM, using social networks usage as a moderating variable. The research method was Structural Equation Modeling, and the data were collected through a survey conducted on 436 respondents from Romania. Findings showed that centrality and density only affect negative eWOM intent, the relationship being stronger at higher levels of network usage. In consequence, influential network me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 76 publications
0
29
0
5
Order By: Relevance
“…Although our results may be effective under certain conditions, they were derived from only one case of predicting skilled nurses. There are a lot of issues in management science contexts to solve: social networks [41] and multiple source data fusion for management decision-making systems in the data transformation era [42]. Therefore, our results should be applied with caution.…”
Section: Discussionmentioning
confidence: 89%
“…Although our results may be effective under certain conditions, they were derived from only one case of predicting skilled nurses. There are a lot of issues in management science contexts to solve: social networks [41] and multiple source data fusion for management decision-making systems in the data transformation era [42]. Therefore, our results should be applied with caution.…”
Section: Discussionmentioning
confidence: 89%
“…This collaboration facilitates open and transparent communication, allowing employees to share their ideas, thoughts, and creative insights easily. Indeed, utilizing online social networks, including electronic word of mouth (eWOM), has been demonstrated to possess significant potential in influencing and modifying individuals' behaviors [56]. Therefore, by harnessing digital platforms, online social networks, and tools, digital leaders can promote brainstorming, idea sharing, and collaborative problem-solving, thus fostering a culture of innovation and creativity within the organization [20].…”
Section: Effects Of Digital Leadership On Individual Creativitymentioning
confidence: 99%
“…According to Anastasiei et al (2023), network centrality and density have a significant impact on the likelihood of participating in electronic word-of-mouth (eWOM) in online social networks. The authors found that individuals with higher network centrality and density were more likely to engage in both positive and negative eWOM.…”
Section: Literature Reviewmentioning
confidence: 99%